SERVERLESS ARCHITECTURE FOR BIG DATA PROCESSING IN ENTERPRISE DATA HUB - Dr. Murugan A , Ganesan S (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In the era of modern utility computing theory, Serverless architecture is the cloud platform concept to hide the server usage from the development community and runs the code on-demand basis. Key objective is to abstract the infrastructure complexities of server management and scaling, but metered payment for processed requests only. This paper provides an algorithm to handle enterprise data hub using efficient serverless architecture for the complex big data query processing. This paper depicts about the experimental advantage of execution time optimization with agile availability and cost reduction of the underlying infrastructure, using new design of Serverless architecture.